2016
DOI: 10.1136/bmjopen-2016-012088
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the Hlabisa pregnancy cohort, KwaZulu-Natal, South Africa

Abstract: PurposeThe Hlabisa pregnancy cohort was established to evaluate the effectiveness of prevention of mother-to-child transmission (PMTCT) guideline revisions. The objectives of the Hlabisa pregnancy cohort are to: (1) provide cohort-level information on maternal health up to 6 weeks postpartum in a high HIV prevalence setting; and to (2) evaluate aspects of PMTCT care that have policy relevance.ParticipantsThe pregnancy cohort is located in primary health clinics in the Hlabisa subdistrict of rural KwaZulu-Natal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Less than one in three 15–19 year olds had tested for HIV in the past 12 months, or visited a clinic in the past six months. Whilst, 20-24-year-olds reports of visiting clinics and HIV testing was associated with their self-reported pregnancies, suggesting that the HIV testing and clinics visits were related to antenatal care in this setting with excellent prevention of mother to child transmission of HIV (PMCT) programme [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less than one in three 15–19 year olds had tested for HIV in the past 12 months, or visited a clinic in the past six months. Whilst, 20-24-year-olds reports of visiting clinics and HIV testing was associated with their self-reported pregnancies, suggesting that the HIV testing and clinics visits were related to antenatal care in this setting with excellent prevention of mother to child transmission of HIV (PMCT) programme [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found a positive association between current use of contraception and knowledge of where to get ART—a proxy measure of health-related knowledge of access to services. This and the poor service usage in younger girls and those who are not yet pregnant may in part reflect the success of the PMTCT programme in reaching women once they become pregnant [ 15 ]. These finding are in keeping with a study in rural Western Cape that also found that having one or more children was associated with increased contraception [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2012, HIV-infected pregnant women attending any one of the 17 antenatal clinics in the Hlabisa HIV Treatment and Care Programme, northern KwaZulu-Natal, South Africa were eligible for inclusion [ 31 ]. Thereafter enrolment was limited to seven clinics within the Africa Centre surveillance area which allowed data linkage (clinics were from the original cohort with 40% of patients generally representative of Hlabisa) [ 32 ]; the additional clinic (Mtubatuba) was one of the busiest in the sub-district [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prevention of mother-to-child transmission (PMTCT) is a significant pathway and an effective HIV testing modality for diagnosing and linking women to ART. The first and the second 90 in the PMTCT programme has been reported to be >90% in South Africa (SA), but knowledge of HIV status and ART initiation prior to pregnancy has been reported to be low [4,5]. In 2016, SA adopted the universal test and treat (UTT) strategy, which makes provision for ART initiation immediately after an HIV-positive test [6].…”
Section: Introductionmentioning
confidence: 99%